(untitled) (ResearchJet Journal of Analysis and Inventions, 2023)
The air quality monitoring in the vicinity of the hospitals waste incinerator is a foremost important strategy for the management and control of air pollution in the near-field of health-care units and nearby areas as well. Therefore, the prime objective of the present study are to monitor ambient air quality with respect to sulphur dioxide (SO2), nitrogen dioxide (NO2) and hydrogen sulfide (H2S) in the vicinity of the maternity hospital waste incinerator in Alkarkh . Three sites have been selected near the incinerator, i.e., 50, 100 m and 200 m along with an unpolluted site approximately 3 km upwind from the waste incineration unit. The air quality monitoring for pre-selected parameters has been carried out during working hours of the incinerator. It has been found that the concentration of pollutants (SO2, NO2 and H2S) increases with downwind in very small amounts and has been observed to be maximum at a downwind distance of 200 m, and the minimum near the source. It was also noted that the observed concentrations of the above-mentioned pollutants were less than the prescribed limits for air quality issued by the Iraqi Ministry of Environment standards.